Engeri abaami okulya awalala awatali waka gye kikosamu endya ennungi mu maka - CGIAR Initiative on Sustainable Animal Productivity (International Livestock Research Institute, 2024)
Cultural norms and practices in Uganda’s central region impact household nutrition. To address these challenges, a Social and Behaviour Change Communication (SBCC) campaign was implemented. The campaign included video skits, community outreach, and the distribution of information, education, and communication (IEC) materials. The campaign aimed to raise awareness about the nutritional value of animal-sourced foods and their contribution to improved nutrition.